Interagir à distance pour nouer un rapport vivant à la langue-culture - Anne Durr (Recherches en didactique des langues et des cultures)
Our research examines four online exchange partnerships based on exolingual interactions between learners in elementary education in France and in Great Britain (8-11-year-olds). Where as young learners have long been excluded from International School Correspondence due to the «  paucity »  of their expression, in this study they demonstrated pro-active behaviours by initiating and benefiting from linksmade between both distant groups.This article focusses on the legitimacy of the social bond that was created between the actors of the projects, situating early language learning in a paradigm centered on the co-learning process (Thibert, 2010). We report in particular on potentially rich learning situations by studying the dynamics which allowed the learners to become aware of their role during the co-learning process.